Virus-free vanilla - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Vanilla plants, freed of a serious virus disease, will soon be offered to farmers in Fiji and elsewhere. The lethal disease, known as a potyvirus, is a serious threat to vanilla production. It appeared in Tonga and then spread to Fiji, where vanilla...